2012
DOI: 10.6113/jpe.2012.12.3.429
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage High-Power-Factor Electronic Ballast with a Symmetrical Class-DE Resonant Rectifier

Abstract: This paper presents the use of a novel, single-stage high-power-factor electronic ballast with a symmetrical class-DE low-dυ/dt resonant rectifier as a power-factor corrector for fluorescent lamps. The power-factor correction is achieved by using a bridge rectifier to utilize the function of a symmetrical class-DE resonant rectifier. By employing this topology, the peak and ripple values of the input current are reduced, allowing for a reduced filter inductor volume of the EMI filter. Since the conduction angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In case of the ZCS-RPFC [17], the envelope of the driving-current is an AM waveform with a modulation index of m = 0.33. The result has shown that the current stresses of the power MOSFETs have been significantly reduced when compared to the previously reported CECS-RPFC and CDECS-RPFC topologies [4], [5], [8], [9]. The bridge rectifier was built using standard-recovery diodes (Fairchild Semiconductor …”
Section: Conduction Loss Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In case of the ZCS-RPFC [17], the envelope of the driving-current is an AM waveform with a modulation index of m = 0.33. The result has shown that the current stresses of the power MOSFETs have been significantly reduced when compared to the previously reported CECS-RPFC and CDECS-RPFC topologies [4], [5], [8], [9]. The bridge rectifier was built using standard-recovery diodes (Fairchild Semiconductor …”
Section: Conduction Loss Analysismentioning
confidence: 99%
“…(CDECS-RPFC) [5], [8]. However, the main drawbacks of the previously proposed CECS-RPFC and CDECS-RPFC topologies are their low efficiency because they suffer from high current stresses in the power switches near the zero-crossing of the line voltage, and the fact that fast recovery diodes are required for the bridge-rectifier.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the conduction loss in the resonant inductor, L P = L P1 = L P1 , is: The parasitic resistance of the secondary leakage inductor, r S , is 640 mΩ, and the maximum value of the resonant current, I r , is given by (19). Thus the conduction loss in the inductor, L lS , is obtained by (20): …”
Section: B Conduction Loss Analysismentioning
confidence: 99%
“…Figure 5(d) illustrates the model of the half bridge class-DE rectifier with a push-pull resonant converter. The input impedance of the class-DE rectifier is represented by a parallel R ip -C ip circuit, which can then be converted into a series combination of the input resistor, R is , and the input capacitor, C is , based on the principle of the half bridge class-DE rectifier [18][19][20], as shown in Fig. 5(e).…”
Section: Analysis Of the Junction Capacitance In Half Bridge Clamentioning
confidence: 99%